Experimentally Calibrated Kinetic Monte Carlo Model Reproduces Organic Solar Cell Current–Voltage Curve. Issue 6 (6th May 2020) - Wilken, Sebastian; Upreti, Tanvi; Melianas, Armantas; Dahlström, Staffan; Persson, Gustav; Olsson, Eva; Österbacka, Ronald; Kemerink, Martijn
Abstract : Kinetic Monte Carlo (KMC) simulations are a powerful tool to study the dynamics of charge carriers in organic photovoltaics. However, the key characteristic of any photovoltaic device, its current–voltage ( J–V ) curve under solar illumination, has proven challenging to simulate using KMC. The main challenges arise from the presence of injecting contacts and the importance of charge recombination when the internal electric field is low, i.e., close to open‐circuit conditions. Herein, an experimentally calibrated KMC model is presented that can fully predict the J–V curve of a disordered organic solar cell. It is shown that it is crucial to make experimentally justified assumptions on the injection barriers, the blend morphology, and the kinetics of the charge transfer state involved in geminate and nongeminate recombination. All of these properties are independently calibrated using charge extraction, electron microscopy, and transient absorption measurements, respectively. Clear evidence is provided that the conclusions drawn from microscopic and transient KMC modeling are indeed relevant for real operating organic solar cell devices. Abstract : Kinetic Monte Carlo simulations are used to describe the current–voltage characteristics of an organic bulk heterojunction solar cell. Excellent agreement between model and experiment is obtained by calibrating the injection barriers, the blend morphology, and the charge transfer recombination rate with data from independent measurement techniques.